Conspiracy Beliefs, Rejection of Vaccination, and Support for hydroxychloroquine: A Conceptual Replication-Extension in the COVID-19 Pandemic Context - Bertin, Paul; Nera, Kenzo; Delouvée, Sylvain (Frontiers in Psychology, 2020)
Many conspiracy theories appeared along with the COVID-19 pandemic. Since it is documented that conspiracy theories negatively affect vaccination intentions, these beliefs might become a crucial matter in the near future. We conducted two cross-sectional studies examining the relations between COVID-19 conspiracy beliefs, vaccine attitudes and intention to be vaccinated against the COVID-19 when a vaccine becomes available. We also examined how these beliefs predicted support for a controversial medical treatment, namely, chloroquine. In an exploratory study 1 (N = 409), two subdimensions of COVID-19 conspiracy beliefs were associated with negative attitude toward vaccine science. These results were partly replicated and extended in a pre-registered study 2 (N = 396). Moreover, we found that COVID-19 conspiracy beliefs (among which, conspiracy beliefs about chloroquine), as well as a conspiracy mentality (i.e., predisposition to believe in conspiracy theories) negatively predicted participants’ intentions to be vaccinated against COVID-19 in the future. Last, conspiracy beliefs predicted support for chloroquine as a treatment for COVID-19. Interestingly, none of the conspiracy beliefs referred to the dangers of the vaccines. Implications for the pandemic and potential responses are discussed.